2017
DOI: 10.1016/j.chemosphere.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate emissions from pyrolysis of mattresses containing polyurethane foam

Abstract: 18This study examined the emissions of powerful asthmatic agents called isocyanates from Additionally, a qualitative search for so far unknown isocyanates was performed in 33 samples from the pyrolysis of FPUF at 300, 400 and 850ºC. It was confirmed that six 34 different aminoisocyanates at 300ºC were evolved, whereas at 400 and 850ºC only five 35 of them were detected. The general trend observed was a decrease of the aminoisocyanate 36 levels with increasing pyrolysis temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
3
19
2
Order By: Relevance
“…89 These results depended on the re temperature, with the highest yield percentage corresponding to the highest burn temperature. 89 Fire tests involving vehicles and their interior, exterior, and engine components have also been investigated for their emissions of isocyanates. 90,91 Signicant amounts of isocyanates were found to be emitted from vehicular res ranging from 0.0059-0.0668 mg m À3 .…”
Section: Materials Combustion From the Built Environmentmentioning
confidence: 95%
See 3 more Smart Citations
“…89 These results depended on the re temperature, with the highest yield percentage corresponding to the highest burn temperature. 89 Fire tests involving vehicles and their interior, exterior, and engine components have also been investigated for their emissions of isocyanates. 90,91 Signicant amounts of isocyanates were found to be emitted from vehicular res ranging from 0.0059-0.0668 mg m À3 .…”
Section: Materials Combustion From the Built Environmentmentioning
confidence: 95%
“…86 In laboratory test res of both exible polyurethane foam and viscoelastic memory foam mattresses, the total yields of isocyanates ranged from 1.43-11.95 mg m À3 and 0.05-6.13 mg m À3 , respectively. 89 Further, it was found that HNCO made up 34-99% and 2-98% of total NCO emissions from exible polyurethane foam and viscoelastic memory foam mattresses, respectively. 89 These results depended on the re temperature, with the highest yield percentage corresponding to the highest burn temperature.…”
Section: Materials Combustion From the Built Environmentmentioning
confidence: 97%
See 2 more Smart Citations
“…[1,2] Although most of the polymers of this group have a high resistance to hydrolysis, these have been studied due to their high biodegradability. [3,4] Among its applications, the production of paints, varnishes, [5] and foams [6] deserves particular attention. They can present different behaviors depending on their synthetic conditions and have considerable permeability, mainly since it can be controlled according to the ratio of their hydrophobic and hydrophilic chain moieties.…”
Section: Introductionmentioning
confidence: 99%